Development of A Web-Based Information System for BUMDes eMHa in Melirang Village, Indonesia - Awwalur Rohmah Cahyaningati; Saffana Assani'; Muhamad Afif Effindi; Taufiqur Rohman (Universitas Trunodjoyo Madura, 2026)
Indonesia’s village-Owned Enterprises (BUMDes) play a strategic role in managing local resources to enhance the economic welfare of rural communities. However, limited access to information has led to low public awareness of their existence, business units, and development. This study aims to design and develop a web-based information system for the Melirang Hebat Village-Owned Enterprise (SIM BUMDes eMHa) as an effective medium for information dissemination and communication. The system was developed using the System Development Life Cycle (SDLC) with the Waterfall model, encompassing requirement analysis, system design, implementation, and testing. The results demonstrate that the proposed system is capable of delivering integrated information on organizational profiles, business units, news, and partnerships. Functional testing showed that all core features operated successfully according to the specified requirements. In addition, the system improved information accessibility and supported more efficient dissemination of BUMDes-related information to the community. The implementation of this system contributes to enhancing transparency, improving information accessibility, and fostering community participation in BUMDes development.